(untitled) (Revista de Ciências Agroveterinárias, 2002)
At UFRGS’s Experimental Station in Eldorado do Sul – RS, an experiment of sod-seeding birdsfoot trefoil cv. São Gabriel in natural pasture was carried out. Were studied three deferment periods (14, 28 and 56 days) and two late summer fertilizations (with and without fertilization) – 120 kg/ha of K2O and 105 kg/ha of P2O5. The DM yield was evaluated with cuttings at 8,0 cm – stubble height. A split-plot experimental design with 4 replications was used: deferment in the main plots and fertilization in the sub-plots. The deferment treatments of 28 and 56 days resulted in higher DM yields than the 14 days treatment, during the fall evaluation. The advantage of the greatest deferment periods also occurred during the spring evaluation, when the 28 days treatment produced the best result whereas the 56 days had an intermediate yield. Higher pasture resting periods, during the summer, resulted in maximum plant population. The late summer topdressing favored the total forage DM yield as well as the birdsfoot trefoil persistence.